Asynchronous circuits : innovations in components, cell libraries and design templates - Moreira, Matheus Trevisan (2016)
For decades now, the synchronous paradigm has been the major choice of the industry for building integrated circuits. Unfortunately, with the development of semiconductor industry, power budgets got tighter and delay uncertainties increased, making synchronous design a complex task. Some of the reasons behind that are the increase in process variability, the losses in wire performance and the uncertainties in the operating condition of devices. These and other factors significantly impact transistor electrical characteristics, making it more complicated to meet timing closure in synchronous systems and compromising power efficiency. The asynchronous paradigm emerges as an efficient alternative to current design approaches, given its inherent high robustness against delay variations and suitability to low-power and high-performance design. However, while a major segment of the design automation industry was developed to support synchronous design, currently, design automation for asynchronous circuits is limited, to say the least. Furthermore, basic components for semi-custom design approaches, typically available in standard cell libraries were optimized to target synchronous implementations and those necessary to support asynchronous design were also left behind. This Thesis proposes new techniques to optimize asynchronous design, from cell to system level. We start by analyzing and optimizing basic components for asynchronous design and then propose new manners of implementing them at the transistor level. The proposed optimizations and novel components allow better exploring power, delay and area trade-offs, providing a guideline for asynchronous designers. We then explore how to design these components as cells for building a library to support semi-custom design. To that extent, we propose a completely automated flow for designing such libraries. This flow comprises transistors sizing and electrical characterization tools, developed in this Thesis, and a layout generation tool, developed by a fellow research group. We also provide a freely available library, designed with the flow, with hundreds of components that were extensively validated with post-layout simulations. Using this library we devised new templates for designing asynchronous circuits at the system level, exploring an automated synthesis solution and expanding design space exploration. Compared to a similar state-of-the-art solution, our latest template provides almost twice better energy efficiency and comprises an original automated method for technology mapping and synthesis optimizations. The contributions of this Thesis allowed the construction of an infrastructure for building asynchronous designs, paving the way to explore their usage to solve contemporary and future challenges in integrated circuit design.